Congenital Disorders of the Human Urinary Tract: Recent Insights From Genetic and Molecular Studies - Woolf, Adrian S.; Lopes, Filipa M.; Ranjzad, Parisa; Roberts, Neil A. (Frontiers in Pediatrics, 2019)
The urinary tract comprises the renal pelvis, the ureter, the urinary bladder and the urethra. The tract acts as a functional unit, first propelling urine from the kidney to the bladder, then storing it at low pressure inside the bladder which intermittently and completely voids urine through the urethra. Congenital diseases of these structures can lead to a range of diseases sometimes associated with fetal losses or kidney failure in childhood and later in life. In some of these disorders, parts of the urinary tract are severely malformed. In other cases, the organs appear grossly intact yet they have functional deficits that compromise health. Human studies are beginning to indicate monogenic causes for some of these diseases. Here, the implicated genes can encode smooth muscle, neural or urothelial molecules, or transcription factors that regulate their expression. Furthermore, certain animal models are informative about how such molecules control the development and functional differentiation of the urinary tract. In future, novel therapies, including those based on gene transfer and stem cell technologies, may be used to treat these diseases to complement conventional pharmacological and surgical clinical therapies.